The Effects of Electromagnetic Field (EMF) on Pregnancy and Postpartum Outcomes: A Systematic Review - Morvarid Irani; Maryam Aradmehr; Seyyedeh Adeleh Rahmanian; Sedigheh Ahmadi (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2023)
Introduction: Humans knowingly or unknowingly are daily exposed to electromagnetic fields and today electricity is an integral part of life. Therefore, the present study was performed with aim to systematically review the studies on the effect of electromagnetic field on pregnancy and postpartum outcomes.Methods: In this review article, which was written based on the PRISMA guidelines, all cohort and case and control studies were searched from the databases of Magiran, Medlib, Web of Science, SID, Iran Medex, Scopus, PubMed, Science Direct, and Google Scholar with keywords of electromagnetic field, mobile phones, mobile phone base stations, watching TV, using Internet, pregnancy outcome, perinatal mortality, preeclampsia, childhood cancers, asthma in offspring, congenital defects, and behavioral and emotional disorders without time limit until May 2022. The quality of the studies was evaluated using the Newcastle-Ottawa criteria. Content analysis was done qualitatively.Results: In this study, 477 articles were extracted. Then, 10 studies with a score of 6 and above were examined with the Newcastle-Ottawa criteria. A review of the evaluated variables in the articles showed that father's exposure to electromagnetic field has been associated with the risk of perinatal mortality, preeclampsia and congenital defects, and the mother's exposure was associated with the risk of asthma, amniotic fluid reduction, decreased motor skills, and delayed neurodevelopment of children. But the pregnant women's living in the vicinity of masts, high voltage cables and mobile phone base stations did not increase congenital anomalies, childhood cancers and behavioral and emotional problems (such as hyperactivity, inattention) in children.Conclusion: Contact of father or mother with electromagnetic waves during pregnancy can cause problems in pregnancy and their children. Therefore, it is recommended to control exposure to electromagnetic fields as much as possible.